The Relationship between Parity and Maternal Age with the Incidence of Anemia in Pregnant Women in the Third Trimester at the Novi Lintas Timur Midwife Clinic, Panyabungan District, Mandailing Regency, Natal 2022 - Mutiara Btr, Elisya (Cattleya Darmaya Fortuna, 2023)
Similar to the intricate flow of a river creating diverse habitats, this study delves into understanding the correlation between parity, maternal age, and the prevalence of anemia among third-trimester pregnant women attending the Novi Lintas Timur Midwife Clinic in Panyabungan District, Mandailing Natal Regency, in 2022. With a cohort of 150 pregnant women as the focal point, this research highlights how the dynamic currents shaped by parity significantly influence the likelihood of experiencing anemia during the final stage of pregnancy. Conversely, the presence of maternal age factors seems to have a negligible impact on this journey. These findings are like a compass for midwives and health researchers to navigate the challenging waters of pregnancy. By understanding the dynamics of parity, they can find more effective intervention strategies in minimizing the risk of anemia in pregnant women. As a reflection of natural harmony, the involvement of health practitioners in monitoring and providing appropriate care to pregnant women with high parity becomes increasingly important to create a healthy and strong flow of life.